Penerapan Model Pembelajaran Quantum Learning Tipe Kinestetik untuk Meningkatkan Hasil Belajar Teknologi Informasi dan Komunikasi (TIK) Siswa Kelas XI IPA 1 SMA Negeri 2 Singaraja Tahun Pelajaran 2012/2013 - Made Suyasa Dwi Putra; Luh Putu Eka Damayanthi; I Made Gede Sunarya; Dessy Seri Wahyuni (Universitas Pendidikan Ganesha, 2013)
This classroom action research aimsto improve students learning results in subject ofInformation Technology and communications byapplying the model of Quantum Learning TypeKinesthetic learning, and study the response of classXI IPA 1 SMAN 2 Singaraja towards theimplementation of Quantum Learning model TypeKinesthetic learning. The subject were students ofclass XI IPA 1 SMAN 2 Singaraja in the secondsemester of academic year 2012/2013, by engagingstudents as many as 32 people. Classroom actionresearch (PTK), which implemented consisted of twocycles. The data collected in this study is the results ofstudents learning in the classical and the students'response to the application of the Quantum LearningType Kinesthetic learning in ICT subject. ICT studentslearning results data obtained through tests in theclassical description (essay), while the studentsresponse data obtained using a questionnaire. Theresults showed that the application of learning modelsQuantum Learning Kinesthetic type of ICT to improvelearning result of students and get a positive responsefrom the students.